The many faces of activated carbon - Mulop, Normah (Faculty of Chemical & Natural Resources Engineering, 1992)
Raw materials containing a high percentage of carbon can be processed and converted to activated carbon which has a large surface area. It is this structure that provides activated carbon with the ability to absorb gases and vapors from gases, and dissolved or dispersed substances from liquids. This unique nature of the activated carbon makes it possible for the carbon to be used for purification purposes and also other applications.